CONCEPTUALIZING THE PRINCIPLES OF SOCIAL MEDIA ENGAGEMENT: TEACHINGS FROM SELECTED VERSES OF SURAH AL-HUJURAAT - Sule, Muhammad Maga (Islamic Communication Journal, 2020)
The speedy advancement in internet technology has revolutionized the use of social media platforms as ways of communication globally. This paper examines the proliferations social media sites in the world and its use among the Muslims.  Unlike traditional media, most of internet based means of social interactions are user-generated. It allows the individual to determine the content of the message with or without censorship or regulation. The liberty to open an account with any site of choice and the freedom it entails, lured some Muslims to surf social media without recourse to or in line with the basic tenets of Islamic teachings.  The paper is a qualitative method where In-Depth Interviews were conducted with seasoned social users.  The researchers purposively selected three participants for the study and interview because they are Muslims and possessed the knowledge about the phenomenon investigated. Some of the findings of the study revealed that some Muslims finds it convenient to share or post unsubstantiated religious messages on social media. Similarly, it has paved way for increasing number of untrained social media preachers. This makes it a delicate tool at the disposal of some of Muslim to fan antagonism among Muslim of creeds and sects in Nigeria. The article concludes that social media is a double-edged sword which side-effects as apparent when Muslim user do not resort to the teachings of Islam as the guiding principle when surfing the social media sites. The unfettered user-generated content of social media in 21st century enables the users to operate outside the ambit of the Islamic convention of social interactions.